Factors Causing the Low Listening Comprehension of English Students on the TOEFL Test at the University Muhammadiyah of Bengkulu - Nora Ristika; Eki Saputra; Ivan Achmad Nurcholis; Ria Angraini (Teaching English and Language Learning English Journal, 2024)
The objective of this research was to find out the factors which are causing and low listening comprehension and to determine the most dominant factor causing low listening comprehension of English students in answering listening comprehension questions on the TOEFL test. This research employed mix method design, which involved collecting and analyzing quantitative and qualitative data. The instrument used in this research were questionnaire and interview. After questionnaire done, the researcher interviewed the students to get secondary data. The results showed that there are two factors causing low listening comprehension which are internal and external factors. The results showed that external factors are the major cause of low listening comprehension with the total mean of 2.54. Three from four aspects presented was received positive respond from the students which are speech delivery, linguistic complexity, and physical setting. On the other hand, lack of experience seems the only one factor appeared from internal factors. The most dominant factor was linguistic complexity with mean of 2.62. The results from interview also confirmed that there are two main causes which are lack of vocabulary and unclear speech of what they heard. There are some suggestions provided in this research. First, it is suggested for teacher/lectures to encourage the students to improve their listening ability. Second, it is suggested for students to enrich vocabulary and their linguistic competences. Finally, it is also suggested to the next researcher to conduct similar research in larger scope. Keywords: Cause, Listening Comprehension, TOEFL.